1993
DOI: 10.1080/00029157.1993.10403049
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Music as a Hypnotic Suggestion

Abstract: We have known of the interaction between music and mood for many years. In this paper, I present a series of case vignettes to illustrate a method using music to affect mood. In hypnosis, I suggested that subjects imagine hearing a piece of music appropriate to a desired emotion, rather like a sound track for a movie. I suggested that the patients vividly recall this music and the accompanying feelings outside of trance when it would be desirable to help them to change their behavior by influencing their emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…An alternative explanation is that the voice enhancement and music interventions functioned in different ways. Whereas music may have reduced arousal, thus rendering the participants more open to contemplative thought processes and imagery suggestions, 28,46 the voice enhancement protocol may have heightened arousal. Clearly, there is a need to combine the imagery measures used in the present study with a psychophysiological measure of arousal (e.g., an electroencephalogram) in order to better elucidate the mechanisms that account for any effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative explanation is that the voice enhancement and music interventions functioned in different ways. Whereas music may have reduced arousal, thus rendering the participants more open to contemplative thought processes and imagery suggestions, 28,46 the voice enhancement protocol may have heightened arousal. Clearly, there is a need to combine the imagery measures used in the present study with a psychophysiological measure of arousal (e.g., an electroencephalogram) in order to better elucidate the mechanisms that account for any effects.…”
Section: Discussionmentioning
confidence: 99%
“…13,18 The hypotheses that follow were based on original research findings relating to sensory deprivation, 30 vocal delivery, 31 and music delivery. 28,30 More specifically, sensory deprivation has been shown to enhance susceptibility to hypnosis, which is akin (although not identical) to guided relaxation, 30 while speech emphasis may alter the reception of instructions. 31 Part of the rationale for the present study is that, although many studies use imagery scripts, none consider the clarity and fidelity of sound delivery.…”
Section: Purpose and Hypothesesmentioning
confidence: 99%
“…Given these overlaps, then, it is surprising that so far only a few studies have investigated the link between music listening and hypnosis. Some of these studies relied on historical sources (Frigau Manning, 2019;Kennaway, 2012), focused on their combined use (Johnson et al, 2017;Kelly, 1993), or else were practically-oriented to advise how music can be used in various phases of hypnosis, including its induction or deepening (Walker, 1992).…”
Section: Music As Hypnosis? a Comparative Network Analysis Of Entranc...mentioning
confidence: 99%
“…Then, the patients were asked to recall this music and the accompanying feelings when outside of the trance state. Using these experiences allows discussion of changing their behavior by influencing their emotional state (Kelly, 1993). While no study has demonstrated a positive association between religious beliefs and reduction of social anxiety, several studies support the contention that religious beliefs reduce various symptoms of anxiety (Azhar, Varma, & Dharap, 1994;Khouzam, 1999).…”
mentioning
confidence: 99%